A heterozygous protein‐truncating RFX6 variant in a family with childhood‐onset, pregnancy‐associated and adult‐onset diabetes. Issue 10 (5th June 2019) - Akiba, K.; Ushijima, K.; Fukami, M.; Hasegawa, Y.
Abstract: Background: Recently, heterozygous RFX6 mutations including p.Arg377Ter were identified in individuals with maturity‐onset diabetes of the young (MODY). Clinical analysis of 36 individuals suggested that RFX6 mutation‐induced MODY is characterized by low penetrance and relatively late onset. However, given the small number of previous reports and the limited clinical information of each case, further studies are necessary to clarify the phenotypic characteristics of RFX6 mutations. Case report: We identified a previously reported p.Arg377Ter variant of RFX6 in a three‐generation family with diabetes. The variant was detected through mutation screening for 30 diabetes‐associated genes. The variant was not found in public databases and was predicted to encode a truncated protein or undergo nonsense‐mediated mRNA decay. The proband showed glycosuria from 8 years of age and was diagnosed with MODY at 10 years of age, before the onset of puberty. She received basal and bolus insulin injection as initial therapy. The proband's mother exhibited glycosuria at 26 years of age when she conceived the first child. The mother was treated with insulin, oral hypoglycaemic drugs and diet. The proband and her mother were negative for islet cell autoantibodies. The maternal grandmother showed glycosuria around 50 years of age and was treated with oral hypoglycaemic drugs alone. Conclusion: This study provides supporting evidence for the causal relationship between heterozygous RFX6 mutations and MODY. Furthermore, our results indicate that phenotypic consequences of RFX6 mutations are highly variable even within a single family, and possibly include childhood‐onset and pregnancy‐associated non‐autoimmune diabetes. What's new?: Heterozygous protein‐truncating variants of RFX6 likely play a role in the development of diabetes in prepubertal children. Phenotypic severities of RFX6 mutations are highly variable, even within a single family. RFX6 mutations may also be associated with diabetes during pregnancy.